The The effect of amplification and reduction techniques on the singability of translated GMS Live songs from Indonesian to English: Efek teknik amplifikasi dan reduksi terhadap singability dalam penerjemahan lagu GMS Live dari Bahasa Indonesia ke Bahasa Inggris - Hizkia Enosa Eldebo; Priska Meilasari (Humaniora Scientia, 2025)
Song translations are different from other translation materials. It not only requires the translator to translate the meaning or intention, but also to adjust to the original tone, rhythm, and intonation. Those requirements are principle especially when the translated song is meant to be sung. A translator often adds or deletes some parts of the lyrics to fit the translated lyric to the tone, rhythm, and intonation. Eighteen translation techniques have been proposed by Molina & Albir (2002). Two of them are amplification and reduction. Amplification includes explicitation, addition, and paraphrase. Reduction includes reduction, implicitation, and deletion. This research aims at analyze how amplification and reduction techniques are applied and influence the singability of GMS Live songs. This research uses the translation technique theory proposed by Molina & Albir (2002). To analyze the singability, the theory of singability proposed by Franzon (2008) is used. This research uses qualitative document analysis through the descriptive approach. It analyzes the data in song lyrics using amplification and reduction techniques. The source of data are five GMS Live songs translated from Bahasa Indonesia to English: Yang Termulia (Glorious God), Dahsyat (So Great), Perkasa (Mighty God), Berkenan BagiMu (Purify Me), and Melodi (Melody). The data analysis result shows that amplification-addition is the dominant technique in this song translation. The techniques chosen actively affected the singability of the song. It is proven by the data analysis result which shows that 80% of the translated lyrics have high level of prosodic match.